Analysis of Traffic Noise at Intersection Considering the Environmental Noise Capacity - Yadav A.; Parida M.; Choudhary P.; Kumar B. (My University, 2025)
Traffic is the main reason for noise pollution at intersections in mid-sized cities. This study identifies nineteen sample intersection locations in Kanpur to analyse the traffic noise level concerning environmental noise capacity. The study utilizes an intersection-specific traffic noise model developed by Yadav et al. (Yadav et al. in India. Noise Mapping, 2023) to calculate equivalent noise levels (Lcal) at intersections. The Lcal varies significantly at these intersections due to variety in the input variables. The noise level has crossed the environmental noise capacity at all locations except LML chauraha. The poorest acoustical climate is reported at Sachan chauraha regarding environmental noise capacity. The noise level should not exceed the environmental noise capacity at any location. Immediate actions are required to reduce the noise level if it crosses the environmental noise capacity. This study can be useful for policymakers to plan strategies to control and mitigate traffic noise at intersections in mid-sized cities considering environmental noise capacity. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2025.